Risk for Vibrio and Paragonimus infections linked to shellfish consumption in Côte d’Ivoire - Traoré, S.G.; Krabi, R.; Odermatt, P.; Utzinger, J.; Costard, Solenne; Makita, K.; Grace, Delia; Koussemon, M.; Bonfoh, Bassirou (2011)
Background: Due to their living environment, shellfish can be contaminated with infectious agents such as Vibrio and Paragonimus which cause Vibrio infection and paragonimiasis, two neglected tropical diseases. The symptoms of paragonimiasis and tuberculosis (TB) are similar, differential diagnosis is therefore necessary for appropriate patient treatment. The objective of this study was to determine whether paragonimiasis and Vibrio infections occur in the south of Côte d’Ivoire, and investigate transmission factors so as to better assess the risk to consumers. Methods: Two cross-sectional surveys were carried out in 2009 and 2010 in 332 patients attending two tuberculosis centres of Abidjan and in 269 schoolchildren of two primary schools in Dabou. Sputum and stools samples were analysed to identify Paragonimus and intestinal parasite eggs. A questionnaire on food consumption habits was administered to patients and schoolchildren. A third survey on the consumption of crustaceans was conducted on 120 randomly selected households in Abidjan. Also, 594 shellfish were purchased from markets in Abidjan and Dabou and 272 were examined for Paragonimus and 322 for Vibrio species. Results: The prevalence of trematode metacercariae in shellfish was 11.8%. The prevalence of Vibrio was 7.8 %. Twenty five Vibrio strains were isolated and their average concentration was 6.26 Log UFC per gram of shellfish. No human case of paragonimiasis was diagnosed in attendants of TB centres and schoolchildren. Among 278 patients in TB centres, 62 had TB, with a higher prevalence amongst males (28.8% vs. 13.9% in females, p = 0.003).The result of 216 patients with negative results to TB diagnostic tests calls for more in-depth studies to elucidate the aetiology of their chronic cough. In the school survey, the prevalence of helminths and intestinal protozoa was 22.3% and 48.8%, respectively. Boys had significantly higher levels of infection. Households consumed shellfish boiled (96.7%) or fried (3.3%). Cooking times reported by respondents were as follows: over an hour in 64.2% of households, 45 to 60 min in 21.7% of cases, 5 to 15 min in 6.8% of households, and between 15 to 45 min in the remaining cases. In addition, 11.7% of households consumed shellfish every day, 45.8% consumed them occasionally and 42.5% rarely. Seven point five percent (7.5%) households had sometimes observed symptoms of food poisoning associated with the consumption of shellfish as porridge. Information collected suggests that crosscontamination of vegetables and other food purchased or prepared at the same time as shellfish might happen. Trematode metacercariae, V. alginolyticus, V. parahaemolyticus and V. cholerae were present in shellfish consumed regularly by humans. Summary: Shellfish preparation practices seem to prevent infection in humans. Changes of practices constitute a major risk factor for transmission. People should cook shellfish well before consumption. They should avoid buying dead crabs. They should also avoid mixing crab with vegetables and lettuce during transport from market and store them separately in the refrigerator.